Changing role of small-scale industry:international,influences, country experiences and lessons for India - Najundan S.
This paper discusses the changing role of small-scale industry, in the context of the adjustments called for by the process of globalisation. The first part of the paper reviews the internally pervasive influences of globalisation, technology revolution and presents eight country case studies of the hanging role of small-scale industry. Indian from the analysis to draw lessons for of the first two parts
Keywords: Small Scale Industry -- India